Health Inequity in People with Intellectual Disabilities: From Evidence to Action Applying an Appreciative Inquiry Approach. Issue 1 (January 2015) - Naaldenberg, Jenneken; Banks, Roger; Lennox, Nick; Ouellette‐Kunz, Hélène; Meijer, Marijke; Lantman‐de Valk, Henny van Schrojenstein
<x xml:space="preserve">Abstract</x> Background The current understanding of health inequities in people with intellectual disabilities does not readily translate into improvements in health status or health care. To identify opportunities for action, the 2013 IASSIDD health SIRG conference organized ten intensive workshops. Materials and methods The workshops each addressed separate topics, a workshop of self advocated was included as well. Workshop reports were analyzed using a qualitative thematical analysis approach. Results A total of 134 participants attended the workshops. The analysis of the workshop reports resulted in three main themes: approach, know‐how and visibility and a pervasive theme, that of person‐centered support. Conclusion Everyone that can contribute to better care should be empowered and facilitated to do so, environments should be accessible and inclusive in nature. Sharing experiences, expertise and data sources within and outside intellectual disabilities care and research were mentioned as ways forward. Strong (policy) visions, felt urgency and shared responsibility are required.